A study of the association between local recurrence and surgical margins in vertical partial laryngectomy for T1 glottic squamous cell carcinoma. (3rd August 2019) - Yang, Yue; Zhou, Jian; Chen, Min; Fang, Yi; Tao, Lei; He, Peijie; Cheng, Lei; Wu, Haitao
Abstract: Background: The effect of surgical margins on local recurrence in T1 glottic squamous cell carcinoma (GSCC) is unclear. Objectives : To investigate the association between surgical margins and local recurrence of T1 GSCC patients with vertical partial laryngectomy (VPL). Materials and methods : We retrospectively studied 117 T1 GSCC patients. Close and negative margins were estimated as distance <5 mm and ≥5 mm. The effect of surgical margins on local recurrence was evaluated. For patients with invasion not reaching muscular-layer, a threshold margin of 2 mm was detected. Results : About 109 patients were exclusively treated by VPL and 8 patients received postoperative radiotherapy. In 109 cases, the posterolateral margins and shortest margins in recurrence group were both lower than no-recurrence group ( p <.01). The ratios of posterolateral margin to average diameter, upper-lower diameter and internal-external diameter in recurrence group were also statistically lower ( p <.05). A threshold margin of 2 mm showed statistical difference on recurrence in patients with invasion not reaching muscular-layer. Conclusions and significance : Posterolateral margin is crucial for local recurrence in T1 GSCC patients treated by VPL. A shortest margin of ≥5 mm should be considered. For the patients with invasion not reaching the muscular-layer, a threshold of 2 mm is enough for safe margin.